Foreign language classroom anxiety / Nor Hidayu Bt Haron and Siti Sarah Azidin - Haron, Nor Hidayu; Azidin, Siti Sarah (2012)
The number of students who report that they feel anxious while learning a foreign language is surprising. According to Worde (1998), more than half of foreign language learners experience some degree of anxiety. The higher level of anxiety and worries will occurring an imbalance of circumstances towards students and may highly influences performance and academic result in those foreign language subject (Zarina, Azizah, Norfazila & Nur Al-Huda, 2007). Thus, this study is conducted to help researchers find out what are the relevant information as related to foreign language classroom anxiety among degree students level 2 and level 3 at UiTM Kedah.as well as to explore the relationship between classroom anxiety level and students' foreign language academic performance. Among the types of anxiety studied were communication apprehension, fear of negative evaluation and test anxiety as related to the classroom activity that may bring anxiety towards the learning process. The instrument used is personally administered questionnaire adapted from Horwitz's (1983) Foreign Language Classroom Anxiety Scale (FLCAS) which was designed to measure the levels of anxiety experienced by the foreign language students based on performance-related tasks.